Attapulgite-Prussian blue / copper Prussian blue analogue nano mimic enzyme as well as preparation method and application thereof
By loading Prussian blue/copper Prussian blue analog nanoparticles on the concave and concave rock stones, the nanosimulated enzymes are formed, which solves the problems of limited effects and high cost of existing antibacterial materials, and achieves efficient, safe and environmentally friendly antibacterial properties.
Patent Information
- Application Number
- CN202411770899.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-04
- Publication Date
- 2025-03-07
AI Technical Summary
Existing antibacterial materials have limited effects on bacterial contamination and infection, and are costly, and have insufficient safety and environmental protection.
The nanoparticles were loaded on the concave and concave rock stone by in situ precipitation method to form a nanocomposite with excellent antibacterial properties.
It improves the biocompatibility and antibacterial activity of antibacterial materials, reduces costs, is safe and environmentally friendly, and is suitable for the addition of antibacterial agents.
Smart Images

Figure CN119563650A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of antibacterial materials, and in particular relates to an attapulgite-Prussian blue / copper Prussian blue analog nano-mimetic enzyme and a preparation method and application thereof. Background Art
[0002] There are a large number of microorganisms in the environment around humans, among which bacteria are the most representative. They are basically everywhere and can reproduce rapidly under suitable temperature and sufficient nutrition conditions, leading to corruption, deterioration, and mold of food and various substances, as well as inflammation, ulceration, and infection of animal and human wounds. It can be said that bacteria threaten the health and life safety of humans, animals and plants all the time. Therefore, antibacterial materials that have an inhibitory effect on the growth and reproduction of microorganisms have become one of the hot topics of research.
[0003] In recent years, nanozymes have become a hot topic of research. Nanozymes are a type of nanomaterial with enzyme properties that have special physical and chemical properties under mild conditions. Compared with natural enzymes or chemical catalysts, nanozymes have catalytic activity without external assistance, and their catalytic activity can be regulated by regulating the size, morphology and other characteristics of the nanozymes. In addition, nanozymes have small storage environment restrictions, a large reaction range, high stability, and low price. They can be used as potential substitutes for natural enzymes in the fields of medicine, chemical industry, food, agriculture, and environment.
[0004] Prussian blue (PB) and Prussian blue analogs (PBAs) have been widely used in catalysis, ion batteries, etc. due to their unique framework structure, three-dimensional pores and the adjustability of metal ions. However, pure PB is small in size, agglomerates, has fewer exposed active sites, and has low efficiency in catalyzing H2O2 electron transfer, which limits its catalytic ability. The one-step synthesis of PB / PBA composites by compounding Prussian blue analogs can enhance its peroxidase catalytic activity and give the material other catalytic activities. Summary of the invention
[0005] The purpose of the present invention is to provide a attapulgite-Prussian blue / copper Prussian blue analog nano-mimetic enzyme and its preparation method and application, so as to solve the problems of bacterial contamination and infection of nano-composite antibacterial agents. The obtained nano-enzyme has good biocompatibility and excellent antibacterial properties, is low in cost, and is safe and environmentally friendly.
[0006] In order to achieve the above object, the present invention adopts the following technical solutions:
[0007] A method for preparing an attapulgite-Prussian blue / copper Prussian blue analog nano-mimetic enzyme comprises the following steps:
[0008] Step 1, weighing a certain amount of ferric chloride, cupric chloride dihydrate, and attapulgite, dispersing the two metal chlorides and attapulgite in a 1.0-5.0 mM citric acid aqueous solution to obtain solution A, stirring until the solution is uniformly dispersed, and ultrasonically dispersing for 15-30 minutes;
[0009] Step 2, weigh a certain amount of potassium ferrocyanide trihydrate, disperse the potassium ferrocyanide trihydrate in a 1.0-5.0 mM citric acid aqueous solution to obtain solution B, stir the two solutions to disperse them evenly, and perform ultrasonic dispersion for 15-30 minutes;
[0010] Step 3: Transfer the two solutions to a constant temperature water bath, add solution B dropwise to solution A, react at constant temperature for 2 to 10 minutes, transfer to room temperature, and continue stirring for 30 minutes;
[0011] Step 4: After the reaction is completed and the mixture is naturally cooled, the obtained sample is centrifuged and the precipitated solid is washed and dried to obtain the attapulgite-Prussian blue / copper Prussian blue analog nanomimetic enzyme.
[0012] Furthermore, in the step 1, the amount of ferric chloride added is 4-16 g / L, and the amount of cupric chloride dihydrate added is 4.25-17 g / L.
[0013] Furthermore, in the step 2, the amount of potassium ferrocyanide trihydrate added is 21-84 g / L.
[0014] The attapulgite-Prussian blue / copper Prussian blue analog nanomimetic enzyme prepared by any of the above preparation methods.
[0015] Furthermore, the modified Prussian blue / copper Prussian blue analog nanoparticles are uniformly loaded on the surface of nanorod-shaped attapulgite, the attapulgite has a length of 200 to 500 nm, and the size of the Prussian blue analog nanoparticles is 5 to 50 nm.
[0016] Furthermore, the above-mentioned attapulgite-Prussian blue / copper Prussian blue analog nano-mimetic enzyme is used in the antibacterial field and biomedical field.
[0017] Compared with the prior art, the present invention has the following technical effects:
[0018] The present invention adopts a simple in-situ precipitation method to synthesize attapulgite-Prussian blue / copper Prussian blue analog nano-mimetic enzyme (PB / CuPBA-APT), and its structure is a nanorod with a large number of nanoparticles. In the preparation process, natural nano-rod-shaped attapulgite mineral is used as a carrier, and the nano-particle Prussian blue and copper Prussian blue analog are loaded on the attapulgite by an in-situ precipitation method, which effectively solves the agglomeration problem of Prussian blue and copper Prussian blue analog nanomaterials, and improves the antibacterial performance and commercial value of low-cost natural clay minerals; at the same time, after the nano-mimetic enzyme contacts with bacteria, there is an iron ion and copper ion dissolution effect, which can act on the bacterial cell membrane and enter the bacteria to cause bacterial metabolic disorders, thereby damaging the bacteria, improving the antibacterial activity of the nano-composite material, and forming a nano-mimetic enzyme with good biocompatibility and high cost performance.
[0019] (1) In the present invention, the copper and iron ion dissolution effect and the enhanced POD enzyme activity and glutathione oxidase performance jointly improve the antibacterial activity of the nanocomposite material, forming a nano-mimetic enzyme with good biocompatibility and excellent hydrogen peroxide responsiveness.
[0020] (2) The nanocomposite antibacterial agent prepared by the present invention is safe, environmentally friendly and has strong drug resistance.
[0021] (3) The attapulgite-Prussian blue / copper Prussian blue analog nanozyme composite antibacterial agent prepared by the present invention can be added to the film as an antibacterial agent. The resulting composite film has an obvious inhibition zone and a good antibacterial effect. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 From top to bottom are the XRD patterns of the attapulgite-Prussian blue / copper Prussian blue analog nanomimetic enzyme (PB / CuPBA-APT) prepared in Example 1, the attapulgite-copper Prussian blue analog (CuPBA-APT) prepared in Comparative Example 2, the attapulgite-Prussian blue (PB-APT) prepared in Comparative Example 1, and attapulgite (APT);
[0023] Figure 2 This is the TEM image of PB-APT nano-mimetic enzyme;
[0024] Figure 3 TEM image of PB / CuPBA-APT nano-mimetic enzyme;
[0025] Figure 4 The results of glutathione oxidation tests of PB-APT nanocomposites, CuPBA-APT nanocomposites and PB / CuPBA-APT nanomimetic enzymes are shown;
[0026] Figure 5The results of the peroxidase activity test of PB-APT nano-mimetic enzyme;
[0027] Figure 6 The results of the peroxidase activity test of PB / CuPBA-APT nano-mimetic enzyme;
[0028] Figure 7 This is a photo of the growth of E. coli colonies on a film made of commercial polyurethane;
[0029] Figure 8 The photo of the growth of Escherichia coli colony in the film made of commercial polyurethane with 5% solid content of PB / CuPBA-APT nanozyme composite antibacterial agent added; DETAILED DESCRIPTION
[0030] The specific contents of the present invention are further explained in detail below in conjunction with embodiments.
[0031] Example 1
[0032] First, 0.32 g of ferric chloride, 0.34 g of cupric chloride dihydrate, and 1.69 g of potassium ferrocyanide trihydrate were weighed respectively, and the two metal chlorides were dispersed in 0.4 g of attapulgite citric acid aqueous solution to obtain solution A, and potassium ferrocyanide was dispersed in citric acid aqueous solution (2 mM) to obtain solution B. The two solutions were stirred until they were evenly dispersed, and then ultrasonically dispersed for 15 minutes; secondly, the two solutions were transferred to a constant temperature heating pot, and solution B was added dropwise to solution A, and the reaction was carried out at a constant temperature for 5 minutes, and then the mixture was moved to room temperature and stirred for 30 minutes; finally, after the reaction was completed and naturally cooled, the obtained sample was centrifuged, and the precipitated solid was washed and dried to obtain attapulgite-Prussian blue / copper Prussian blue analogues.
[0033] Example 2
[0034] First, 0.64 g of ferric chloride, 0.68 g of cupric chloride dihydrate, and 1.69 g of potassium ferrocyanide trihydrate were weighed respectively, and the two metal chlorides were dispersed in 0.4 g of attapulgite citric acid aqueous solution to obtain solution A, and potassium ferrocyanide was dispersed in citric acid aqueous solution (2 mM) to obtain solution B. The two solutions were stirred until they were evenly dispersed, and then ultrasonically dispersed for 15 minutes; secondly, the two solutions were transferred to a constant temperature heating pot, and solution B was added dropwise to solution A, and the reaction was carried out at a constant temperature for 5 minutes, and then the mixture was moved to room temperature and stirred for 30 minutes; finally, after the reaction was completed and naturally cooled, the obtained sample was centrifuged, and the precipitated solid was washed and dried to obtain attapulgite-Prussian blue / copper Prussian blue analogues.
[0035] Example 3
[0036] First, 0.64 g of ferric chloride, 0.32 g of cupric chloride dihydrate, and 1.69 g of potassium ferrocyanide trihydrate were weighed respectively, and the two metal chlorides were dispersed in 0.4 g of attapulgite citric acid aqueous solution to obtain solution A, and potassium ferrocyanide was dispersed in citric acid aqueous solution (2 mM) to obtain solution B. The two solutions were stirred until they were evenly dispersed, and then ultrasonically dispersed for 15 minutes; secondly, the two solutions were transferred to a constant temperature heating pot, and solution B was added dropwise to solution A, and the reaction was carried out at a constant temperature for 5 minutes, and then the mixture was moved to room temperature and stirred for 30 minutes; finally, after the reaction was completed and naturally cooled, the obtained sample was centrifuged, and the precipitated solid was washed and dried to obtain attapulgite-Prussian blue / copper Prussian blue analogues.
[0037] Example 4
[0038] First, 0.32 g of ferric chloride, 0.34 g of cupric chloride dihydrate, and 0.84 g of potassium ferrocyanide trihydrate were weighed respectively, and the two metal chlorides were dispersed in 0.4 g of attapulgite citric acid aqueous solution to obtain solution A, and potassium ferrocyanide was dispersed in citric acid aqueous solution (2 mM) to obtain solution B. The two solutions were stirred until they were evenly dispersed, and then ultrasonically dispersed for 15 minutes; secondly, the two solutions were transferred to a constant temperature heating pot, and solution B was added dropwise to solution A, and the reaction was carried out at a constant temperature for 5 minutes, and then the mixture was moved to room temperature and stirred for 30 minutes; finally, after the reaction was completed and naturally cooled, the obtained sample was centrifuged, and the precipitated solid was washed and dried to obtain attapulgite-Prussian blue / copper Prussian blue analogues.
[0039] Comparative Example 1
[0040] First, 0.64 g of ferric chloride and 1.69 g of potassium ferrocyanide trihydrate were weighed respectively, and the ferric chloride was dispersed in 0.4 g of attapulgite citric acid aqueous solution to obtain solution A, and potassium ferrocyanide was dispersed in citric acid aqueous solution (2 mM) to obtain solution B. The two solutions were stirred until they were evenly dispersed, and then ultrasonically dispersed for 15 minutes; secondly, the two solutions were transferred to a constant temperature heating pot, and the B solution was added dropwise to the A solution, and the reaction was carried out at a constant temperature for 5 minutes, and then the mixture was moved to room temperature and stirred for 30 minutes; finally, after the reaction was completed and naturally cooled, the obtained sample was centrifuged, and the precipitated solid was washed and dried to obtain attapulgite-Prussian blue.
[0041] Comparative Example 2
[0042] First, 0.68 g of cupric chloride dihydrate and 1.69 g of potassium ferrocyanide trihydrate were weighed respectively, and the cupric chloride was dispersed in 0.4 g of attapulgite citric acid aqueous solution to obtain solution A, and potassium ferrocyanide was dispersed in citric acid aqueous solution (2 mM) to obtain solution B. The two solutions were stirred until they were evenly dispersed, and then ultrasonically dispersed for 15 minutes; secondly, the two solutions were transferred to a constant temperature heating pot, and the B solution was added dropwise to the A solution, and the reaction was carried out at a constant temperature for 5 minutes, and then the mixture was moved to room temperature and stirred for 30 minutes; finally, after the reaction was completed and naturally cooled, the obtained sample was centrifuged, and the precipitated solid was washed and dried to obtain the attapulgite-copper Prussian blue analogue.
[0043] Figures 1 to 8 These are the characterization results of the attapulgite-Prussian blue / copper Prussian blue analog (PB / CuPBA-APT) nanocomposite enzyme mimics. Figure 1 From top to bottom are the XRD patterns of the PB / CuPBA-APT nanomimetic enzyme prepared in Example 1, the CuPBA-APT prepared in Comparative Example 2, the PB-APT prepared in Comparative Example 1, and attapulgite (APT); Figure 1 The spectra of the three composite materials all clearly showed the diffraction peak of attapulgite, which matched that of pure APT; and in the XRD spectrum of the PB-APT nanocomposite antibacterial agent, obvious characteristic peaks of PB appeared (JCPDS 01-0239), and the PB / CuPBA-APT nanocomposite antibacterial agent had the same diffraction peaks as PB-APT and CuPBA-APT, indicating the successful preparation of the PB / CuPBA-APT nanomimetic enzyme.
[0044] Figure 2 This is the TEM image of PB-APT. Figure 3 TEM image of PB / CuPBA-APT; Figure 2 and Figure 3 It can be seen that the natural mineral clay attapulgite has a nanorod-like structure with a length of 400-500nm and a width of about 10nm, and has a very large aspect ratio. It can be observed that there are a large number of nanoparticles on it, and they are relatively uniform. Combined with the XRD test results, it can be seen that these nanoparticles are PB nanoparticles and CuPBA nanoparticles, which further illustrates the successful preparation of PB / CuPBA-APT nanomimetic enzyme.
[0045] Figure 4 As for the GSH (glutathione) oxidation activity of PB-APT, CuPBA-APT and PB / CuPBA-APT, it can be observed that PB-APT itself does not have GSH oxidase activity. After being compounded with CuPBA, the GSH oxidase activity of the obtained PB / CuPBA-APT is greatly improved.
[0046] Figure 5 , Figure 6 When the concentration of PB-APT and PB / CuPBA-APT was 60μg / mL, different volumes of H2O2 (100mM) treated tetramethylbenzidine (TMB) were added and the absorbance was measured at 652nm. It can be found that with the increase of H2O2 volume, the slope of absorbance change with time increases, and PB-APT is much weaker than PB / CuPBA-APT. The double reciprocal of the initial reaction rate of H2O2 and the substrate concentration is calculated to obtain the V of PB-APT. max 2.07×10 -8 M.s -1 , K m The V of PB / CuPBA-APT is 29.62mM. max 2.83×10 -8 M.s -1 , K m Compared with PB-APT, PB / CuPBA-APT has a larger V max and smaller K m , which means that PB / CuPBA-APT has a faster reaction rate and better substrate affinity.
[0047] Figure 7 , Figure 8 They are films made of commercial polyurethane and polyurethane films with PB / CuPBA-APT nano-mimetic enzyme added with a solid content of 5%. After adding PB / CuPBA-APT nano-mimetic enzyme with a solid content of 5%, the area of the inhibition zone increased by 33.3%, and the antibacterial performance was greatly improved.
[0048] The above are only preferred embodiments according to the embodiments of the present invention, and are not intended to limit the embodiments of the present invention. For those skilled in the art, various modifications and changes may be made according to the embodiments of the present invention. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the embodiments of the present invention shall be included in the protection scope of the embodiments of the present invention.
Claims
1. A method for preparing a attapulgite-Prussian blue / copper Prussian blue analog nano-mimetic enzyme, characterized in that: The following steps are involved: Step 1, weighing a certain amount of ferric chloride, cupric chloride dihydrate, and attapulgite, dispersing the two metal chlorides and attapulgite in a 1.0-5.0 mM citric acid aqueous solution to obtain solution A, stirring until the solution is uniformly dispersed, and ultrasonically dispersing for 15-30 minutes; Step 2, weigh a certain amount of potassium ferrocyanide trihydrate, disperse the potassium ferrocyanide trihydrate in a 1.0-5.0 mM citric acid aqueous solution to obtain solution B, stir the two solutions to disperse them evenly, and perform ultrasonic dispersion for 15-30 minutes; Step 3: Transfer the two solutions to a constant temperature water bath, add solution B dropwise to solution A, react at constant temperature for 2 to 10 minutes, transfer to room temperature, and continue stirring for 30 minutes; Step 4: After the reaction is completed and the mixture is naturally cooled, the obtained sample is centrifuged and the precipitated solid is washed and dried to obtain the attapulgite-Prussian blue / copper Prussian blue analog nanomimetic enzyme.
2. The method for preparing the attapulgite-Prussian blue / copper Prussian blue analog nano-mimetic enzyme according to claim 1, characterized in that: In the step 1, the amount of ferric chloride added is 4-16 g / L, and the amount of cupric chloride dihydrate added is 4.25-17 g / L.
3. The method for preparing the attapulgite-Prussian blue / copper Prussian blue analog nano-mimetic enzyme according to claim 1, characterized in that: The amount of potassium ferrocyanide trihydrate added in step 2 is 21-84 g / L.
4. The attapulgite-Prussian blue / copper Prussian blue analog nanomimetic enzyme prepared according to any one of the preparation methods described in claims 1 to 3.
5. The attapulgite-Prussian blue / copper Prussian blue analog nanomimetic enzyme according to claim 4, characterized in that: The modified Prussian blue / copper Prussian blue analog nanoparticles are uniformly loaded on the surface of nanorod-shaped attapulgite, the length of the attapulgite is 200-500nm, and the size of the Prussian blue analog nanoparticles is 5-50nm.
6. Application of the attapulgite-Prussian blue / copper Prussian blue analog nano-mimetic enzyme as claimed in claim 4 in the field of antibacterial and biomedical treatment.
Citation Information
Patent Citations
High-activity and high-yield attapulgite compound enzyme as well as preparation method and application thereof
CN116603543A
Copper-doped Prussian blue nano-enzyme as well as preparation method and application thereof
CN118558355A